Plasma levels of atrial and brain natriuretic peptides in apparently healthy subjects: Effects of sex, age, and hemoglobin concentration - Hamada, Mareomi; Shigematsu, Yuji; Takezaki, Masayuki; Ikeda, Shuntaro; Ogimoto, Akiyoshi (International journal of cardiology, 2017)
To examine whether the use of one value of natriuretic peptides to define “normal” is appropriate in all individuals, and to assess the influence of sex, age, and other variables on atrial and brain natriuretic peptides (ANP, BNP) levels. A total of 1375 apparently healthy people (women:155, men:1220), aged 18–70years were enrolled. Both ANP and BNP levels were higher in women than in men (ANP: 12.50±6.82pg/mL vs 8.18±4.19pg/mL; BNP: 9.85±7.63pg/mL vs 7.03±6.97pg/mL). The subjects were divided into three age groups: group I, 18–30years; group II, 30–50years; group III, 50–70years. First, the influence of age on ANP and BNP levels was examined. In women, both ANP and BNP levels were higher in groups II and III than those in group I. In men, ANP and BNP levels increased with age. Second, sex differences in ANP and BNP levels due to age were examined. ANP level was higher in women than that in men in all age groups. BNP level was higher in women than that in men in groups I and II. Multivariate analysis indicated that both ANP and BNP levels were influenced by age, hemoglobin level, and platelet counts. Because ANP and BNP levels in healthy subjects are influenced by sex, age, and hemoglobin levels, the use of a single value to define “normal” in all individuals is not appropriate.